2012
DOI: 10.5665/sleep.2110
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Collapsibility and Genioglossus Activity in Adolescents during Sleep

Abstract: Obese controls have vigorous upper airway neuromuscular responses during sleep. Upper airway reflexes normally decline during adolescent development. It is speculated that obese adolescents without OSAS maintain protective upper airway reflexes during adolescent development, whereas those who go on to develop OSAS do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 46 publications
3
34
0
1
Order By: Relevance
“…[30][31][32][33][34][35][36] Children with OSA are unable to activate airway tone to maintain airway patency. [37][38][39] The lack of sensation of nasal airflow, as by adenotonsillar hypertrophy or nasal obstruction common in the pediatric population, is associated with increased nasopharyngeal resistance and contributes to OSA, [40][41][42][43][44][45] suggesting that sensation of nasal airflow reduces airway resistance and elicits compensatory increase in pharyngeal tone. 36,46 Therefore, the delivery of heated and humidified air to the nasopharynx at higher than usual flow rates may activate, or reactivate, the protective airway reflex via nasopharyngeal mechanoreceptor or thermoreceptor stimulation, as well as reduce irritation, swelling, and congestion associated with dryness.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] Children with OSA are unable to activate airway tone to maintain airway patency. [37][38][39] The lack of sensation of nasal airflow, as by adenotonsillar hypertrophy or nasal obstruction common in the pediatric population, is associated with increased nasopharyngeal resistance and contributes to OSA, [40][41][42][43][44][45] suggesting that sensation of nasal airflow reduces airway resistance and elicits compensatory increase in pharyngeal tone. 36,46 Therefore, the delivery of heated and humidified air to the nasopharynx at higher than usual flow rates may activate, or reactivate, the protective airway reflex via nasopharyngeal mechanoreceptor or thermoreceptor stimulation, as well as reduce irritation, swelling, and congestion associated with dryness.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents aged 12-16 years were recruited as part of a larger study evaluating the pathophysiology of OSAS (19)(20)(21)(22). Adolescents with OSAS were recruited from the Sleep Center at CHOP.…”
Section: Participantsmentioning
confidence: 99%
“…However, these structural factors cannot fully explain the degree of upper airway collapsibility (1,2). Studies have shown that upper airway neuromotor tone and reflexes during sleep play an important role in maintaining airway patency during sleep in the pediatric population (3,4). Recently, it has been shown that central nervous system processing of upper airway respiratory stimuli is abnormal during sleep in children with OSAS (5).…”
mentioning
confidence: 99%